Earmarking Taxation and Compliance: Some Evidence from Car Ownership in Italy - Lory Barile; Giulio Grossi; Patrizia Lattarulo; Maria Grazia Pazienza (Economies)
This study focuses on tax evasion within the framework of earmarking taxation, specifically focusing on the evasion of car ownership taxes. We utilize a unique and extensive micro-database that combines information on regular payments of the tax due, late payments following friendly warnings, and non-payment of vehicle ownership taxes, integrated with fiscal data, individual data, and municipal-level data. The empirical analysis examines individual, socio-economic, and institutional factors related to this issue. Drawing a rich dataset from the 2014 Tuscany car tax, we employ a multilevel logistic model for our empirical investigation. Our findings reveal that tax evasion poses an equity problem, as the inclination to evade vehicle ownership taxes is concentrated among specific demographic categories and types of vehicles. We also suggest that regional-level policies, such as friendly warnings, could be more effective if implemented with greater rigour. Lastly, our results indicate that reinforcing civic responsibility and enhancing institutional and political quality could prove particularly beneficial in enhancing tax compliance.